2016
DOI: 10.1002/fuce.201500167
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Proton Dynamics in Catalytic Layer of HT‐PEFC

Abstract: The present study focuses on structural and dynamical properties of the catalytic layer for high‐temperature polymer electrolyte fuel cells (HT‐PEFC). The catalytic layer is a composite material containing nanoporous carbon, poly(tetrafluoroethylene) (PTFE) and platinum (Pt) nanoparticles. The structure of the catalyst is investigated using small angle X‐ray scattering (SAXS) following different preparation steps of the electrodes: pure carbon support, platinum/carbon (Pt/C) powder and finally, complete cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…2,5,6,25 In phosphate containing systems QENS has e.g. recently been used to study the proton diffusion in solid CsH 2 PO 4 , 52 the electrode reaction of phosphoric acid fuel cells 53 and neat phosphoric acid from solid to melt. 2,40,41 For CsH 2 PO 4 it was pointed out by Ishikawa et al that 1 H NMR relaxation, 1 H PFG-NMR and QENS assess different aspects of proton dynamics in phosphates.…”
Section: Quasielastic Neutron Scattering (Qens)mentioning
confidence: 99%
“…2,5,6,25 In phosphate containing systems QENS has e.g. recently been used to study the proton diffusion in solid CsH 2 PO 4 , 52 the electrode reaction of phosphoric acid fuel cells 53 and neat phosphoric acid from solid to melt. 2,40,41 For CsH 2 PO 4 it was pointed out by Ishikawa et al that 1 H NMR relaxation, 1 H PFG-NMR and QENS assess different aspects of proton dynamics in phosphates.…”
Section: Quasielastic Neutron Scattering (Qens)mentioning
confidence: 99%
“…The two main components, the proton conducting membrane (PBI doped with phosphoric acid) and the electrode layer, have been studied with quasielastic neutron scattering, small angle X-ray and neutron scattering and electron microscopy [8,9]. The SANS experiments, although with a fuel cell not in operation, showed that the major scattering contribution of this rather thick sample comes from the MEA itself (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The uncertainties due to background scattering of the fuel cell however make us believe that a more detailed discussion of the differences needs further experiments with a better knowledge of the background situation. Future work needs to allow assess the fuel cell effects properly, and the results of operando fuel cell measurements have to be related to corresponding measurements of the proton conducting membrane alone with QENS [1,11] and NMR [12] and NMR measurements of phosphoric acid alone [13] and measurements of the electrode layer [8]. Here we only want to focus on relative changes under the same conditions, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The structure of HT-PEFC catalyst layers has been analyzed with SAXS, SANS and transmission electron microscopy (TEM) with samples of the same kind (20 and 60 % Pt) [13,19,20]. In these 2 instances of the Beaucage model, with R g,0 of about 10 Å from the Pt particles, and a larger length scale R g,1 500 Å of the supporting structure, with a fractal power law decay with an exponent P close to 4 indicating a compact structure.…”
Section: Discussionmentioning
confidence: 99%
“…The gas diffusion elecrodes are prepared as described in Ref. [11][12][13] and for details we refer to this reference. In brief, Pt nanoparticles supported on carbon with 20 and 60 wt% Pt were dissolved and mixed with PTFE as an ink, which then was casted with a doctor blade technique onto a commercially available gas diffusion layer.…”
Section: Methodsmentioning
confidence: 99%